METODE BERMAIN KREATIF DALAM PENANGANAN AWAL ANAK DENGAN GEJALA GANGGUAN EMOSI - Ellyana Ilsan Eka Putri; Riris Rofiqo Holida (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study describes the method of creative play applied to learning activities in RA Darul Amin Panjen in Handling Children with Symptoms of Emotional Disorders. Explain how to apply creative play methods and their effects on the development of early childhood emotions. This research use desciptive qualitative approaching. The subjects in this study were 10 children consist of 3 boys and 7 girls in group A at RA Darul Amin. Data sources were obtained from observation, interviews, documentation and triangulation. The results of the analysis were carried out by data reduction, data presentation and conclusion drawing. The Research Results can be concluded that the Creative Play Method can be applied as an initial step to deal with and prevent the emergence of symptoms of emotional disorder in children aged 4-5 years at RA Darul Amin Panjen. This is proven by the change of children communication patterns and behavior significantly.